2017
DOI: 10.4103/jfmpc.jfmpc_357_16
|View full text |Cite
|
Sign up to set email alerts
|

Can mid-upper arm circumference and calf circumference be the proxy measures to detect undernutrition among elderly? Findings of a community-based survey in rural Puducherry, India

Abstract: Introduction:Major proportion of the elderly with under nutrition is undetected in the community. One of the feasible ways to detect under nutrition among elderly would be screening in the field settings. in this study, we aimed to identify the utility of alternate anthropometric measures such as mid-upper arm circumference (MUAC), calf circumference, and skin fold thickness in identifying under nutrition among elderly.Materials and Methods:A community-based cross-sectional survey was done among elderly in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
(15 reference statements)
2
19
0
3
Order By: Relevance
“…Using other Nutritional status assessment, such as: MUAMC and TST shown that malnutrition was frequent among CRC patients, especially among male patients, and this results is due to the presence of receptors of epinephrine alpha in large numbers in thigh regions in females, these receptors inhibit lipolysis which explains the higher percentage of body fat in females than in males ( 25 ). This result is similar to the results found in an Indian study ( 26 ). Using NRI showed a higher percentage of moderate malnutrition among males, and a higher percentage of severe malnutrition among females.…”
Section: Discussionsupporting
confidence: 92%
“…Using other Nutritional status assessment, such as: MUAMC and TST shown that malnutrition was frequent among CRC patients, especially among male patients, and this results is due to the presence of receptors of epinephrine alpha in large numbers in thigh regions in females, these receptors inhibit lipolysis which explains the higher percentage of body fat in females than in males ( 25 ). This result is similar to the results found in an Indian study ( 26 ). Using NRI showed a higher percentage of moderate malnutrition among males, and a higher percentage of severe malnutrition among females.…”
Section: Discussionsupporting
confidence: 92%
“…In this way, the present study showed significant correlations between lower leg MT and calf circumference ( r = 0.545, p = 0.016), but not arm circumference. On the other hand, arm circumference is a parameter that can be used to detect undernutrition in elderly people [17]. The present study showed an association between lower leg EI and arm circumference ( r = −0.478, p = 0.038).…”
Section: Discussionsupporting
confidence: 50%
“…However, lower limb muscles are the most important muscle groups for functional independence in older adults [16]. Muscle thickness and echo intensity ultrasound parameters in lower limb muscles have been associated with functional capacity in older adults [17,18,19]. For this reason, it is important to investigate the interactions between lower limb muscle ultrasound parameters and nutritional status in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition status was measured by differences in midarm circumferences, calf circumference, triceps skinfolds thickness, and Mini Nutritional Assessment (MNA). Cutoff values of 24 cm, 27 cm, and 3 cm were used to detect malnutrition with midarm circumference, calf circumference, and triceps skinfold thickness, respectively . Given that blood biomarkers for malnutrition remain widely used in clinical practice, we also included hemoglobin and serum albumin level for nutrition biomarkers in older adults, as suggested by a recent systematic review …”
Section: Methodsmentioning
confidence: 99%